Female Students in Engineering. Geology, Mining, and Petroleum Engineering Comparison - Lažnjak, Jasminka (Array, 1997)
Engineering profession went last decades trough process of feminization, but not equaly. The article is focused on one of the most male dominant profession - mining, geology, and petroleum engineering (MGPE). This study will examine the percentage of female students and graduates from mining college and their achievement on undergraduate level in eleven years period. Data show a significant differences in female students enrolment among geology (35% female) and mining and petroleum engineering (14% women). The theoretical background in explanation why women are marginal group in MPE is based on two different approaches: technological determinism and social shaping of technology. The role of technology in altering of women postion in society is significant. The social construction of technology thesis stresses social factors and interests of main actors which in this case include the reproduction of traditional value system and occupational segregation.